MENELUSURI NILAI-NILAI KARAKTER DALAM PANTUN - Hasim, Abdul (PEDAGOGIA, 2016)
The purpose of education in Indonesia from time to time always includes the character or moral values in the students. This is no exception also in the latest curriculum changes, better known as Kurtilas. Changes in the educational curriculum agendas that regularly take place in order to improve the quality of education in Indonesia with the main theme of building a nation's character. Of course this should be implemented in a more operational level, ie in learning activities. Of the many learning materials, learning rhymes turns deviate huge potential in an effort to build character or good values, with values or moral message contained in rhyme.